2017
DOI: 10.1016/j.trsl.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenylquinoxalinone CFTR activator as potential prosecretory therapy for constipation

Abstract: Constipation is a common condition for which current treatments can have limited efficacy. By high-throughput screening, we recently identified a phenylquinoxalinone activator of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel that stimulated intestinal fluid secretion and normalized stool output in a mouse model of opioid-induced constipation. Here, we report phenylquinoxalinone structure-activity analysis, mechanism of action, animal efficacy data in acute and chronic models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Tenapanor given orally at 5 mg/ kg also partially prevented loperamide-induced reduction in stool weight, pellet number, and water content. The magnitude of these responses is similar to that seen with very high doses of the approved drug linaclotide (26,27). Remarkably, coadministration DRA inh -A250 and tenapanor completely prevented loperamide-induced constipation, suggesting an additive effect of slc26a3 and NHE3 inhibition Summary data for studies as in A with data normalized to control conditions (white bars) (mean ± SEM, n = 6 for plate reader assays, and n = 10-28 for single cell assays, differences not significant by two-tailed t test).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Tenapanor given orally at 5 mg/ kg also partially prevented loperamide-induced reduction in stool weight, pellet number, and water content. The magnitude of these responses is similar to that seen with very high doses of the approved drug linaclotide (26,27). Remarkably, coadministration DRA inh -A250 and tenapanor completely prevented loperamide-induced constipation, suggesting an additive effect of slc26a3 and NHE3 inhibition Summary data for studies as in A with data normalized to control conditions (white bars) (mean ± SEM, n = 6 for plate reader assays, and n = 10-28 for single cell assays, differences not significant by two-tailed t test).…”
Section: Resultssupporting
confidence: 61%
“…Three prosecretory drugs that activate Cl -channels have been approved: lubiprostone, a prostaglandin derivative that indirectly activates CFTR and chloride channel 2 (ClC-2); linaclotide, a peptide agonist of the guanylate cyclase C receptor that indirectly activates CFTR; and plecanatide, a uroguanylin analog that also acts as an agonist of the guanylate cyclase C receptor (30). Our group recently reported CFTR activators with marked pro-secretory action and improved efficacy over lubiprostone and linaclotide in experimental animal models of constipation (26,27,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Loss-of-function mutations in CFTR cause cystic fibrosis, and CFTR overactivation causes certain secretory diarrheas including cholera and Travelers’ diarrhea. 2 CFTR is considered an important drug target, with activators of CFTR of potential benefit for constipation, 3,4 dry eye, 5 inflammatory lung disorders, 6 and cholestatic liver disease; inhibitors of wild-type CFTR may be useful for treatment of certain secretory diarrheas and polycystic kidney disease; 7,8 and correctors and potentiators of mutant CFTRs have been shown to be useful for treatment of cystic fibrosis. 9 …”
Section: Introductionmentioning
confidence: 99%
“…3 Phenylquinoxalinone 4 activated CFTR chloride conductance with an EC 50 of ∼200 nM and showed no apparent off-target actions or toxicity following chronic administration in mice. In a follow-up study, 4 4 was shown by patch-clamp and biochemical studies to target CFTR directly and was demonstrated to activate CFTR in human enterocytes and normalize stool parameters in mouse models of acute and chronic constipation. Side-by-side comparisons of intestinal fluid secretion and stool output in constipation models showed greater efficacy of 4 than supramaximal doses of the FDA-approved drugs lubiprostone and linaclotide.…”
Section: Introductionmentioning
confidence: 99%